Towards making optimal decisions in the Serbian Army for reducing the effects of ordnance explosions - Stojanović, Dejan S.; Stojilković, Petar Lj. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The paper proposes organising a professional team of the Serbian Army members who would, in addition to their regular duties, assess the hazards, risk and threats of possible explosions of explosive materials and suggest accordingly optimal decsions to decision makers. Operational meetings are defined, followed by the explanation of the importance of training a team of experts for making optimal decisions, in order to reduce the security threat to people and property from the effects of the explosion of explosive materials. The research results and the discussion point to the lack of involvement of other members of the Serbian Army in the basic command functions when proposing solutions for making optimal decisions. It has been emphasized that the findings of the research process would increase the security and safety of all members of the Serbian Army from the effects of explosions of explosive materials.